Verhindert die Unabhängigkeit der Zentralbank politische Konjunkturzyklen? - Ralph Solveen (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
– Two theoretical modeis are developed. One describes the behavior of monetary policy before elections, in case of policy instruments being controlled by the government. The other one discusses the effects of a change in the ruling party, if parties differ in the weight they attribute to Inflation in their loss function. Next, the propositions of the modeis are tested for the industrial countries. Furthermore, it is tested whether the independence of the central bank prevents such politicaüy motivated cycles in monetary policy. Simple empirical methods and estimated reaction functions of the G7-countries are applied in this investigation. The empirical evidence is mixed. There is some evidence of opportunistic cycles in monetary policy. But the evidence of positive effects of the independence of the central bank is rather weak. Scarcely any evidence is found of partizan cycles in monetary policy.
Keywords: C22; E58; 330; Zentralbankautonomie; Politischer Konjunkturzyklus; G-7-Staaten; Theorie